Human, Pig, and Mouse Interferon-Induced Transmembrane Proteins Partially Restrict Pseudotyped Lentiviral Vectors - Hornick, Andrew L. (Hum Gene Ther, 2016)
Lentiviral vectors are increasingly used in clinical trials to treat genetic diseases. Our research has focused on strategies to improve lentiviral gene transfer efficiency in the airways. Previously we demonstrated that a feline immunodeficiency virus (FIV)-based lentiviral vector pseudotyped with the baculovirus envelope glycoprotein GP64 (GP64-FIV) efficiently transduced mouse nasal epithelia in vivo but transduced mouse intrapulmonary airways with 10-fold less efficiency. Here, we demonstrate that members of a family of proteins with antiviral activity, interferon-induced transmembrane proteins (IFITMs), are more highly expressed in mouse intrapulmonary airways as compared with mouse nasal airways. Using GP64- and VSV-G (vesicular stomatitis virus G glycoprotein)-pseudotyped FIV, we show that expression of mouse IFITM1, IFITM2, and IFITM3 restricts gene transfer. Further, we show that both the nasal and intrapulmonary airways of IFITM locus knockout mice are more efficiently transduced with GP64-FIV than their heterozygous littermates. In anticipation of transitioning our studies into pig models of airway disease and clinical trials in humans, we investigated the ability of pig and human IFITMs to restrict lentiviral gene transfer. We observed that both human and pig IFITMs partially restricted both VSV-G-FIV and GP64-FIV transduction in vitro. Previous studies have focused on IFITM-mediated restriction of replication-competent wild-type viruses; however, these results implicate the IFITM proteins as restriction factors that can limit lentivirus-based vector gene transfer to airway epithelia. The findings are relevant to future preclinical and clinical airway gene therapy trials using lentivirus-based vectors.